2012
DOI: 10.1007/s10566-011-9169-z
|View full text |Cite
|
Sign up to set email alerts
|

If Only “a Rose by Any Other Name Would Smell as Sweet”: A Systematic Review on the Impact of Youth Work for Young People

Abstract: Background Internationally there is an increasing commitment and investment to sup-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Previous literature reviews in the field of professional youth work have already revealed the absence of rigorously conducted evaluative research of the methodological process and impact of professional youth work across the globe (McGregor, 2015;Mundy-McPherson et al, 2012). A recent narrative review of the available research evidence on the impact and factors contributing to impact of open access youth work upon young people (Hill, 2020) proved helpful in terms of selecting studies that were investigating the same topic.…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature reviews in the field of professional youth work have already revealed the absence of rigorously conducted evaluative research of the methodological process and impact of professional youth work across the globe (McGregor, 2015;Mundy-McPherson et al, 2012). A recent narrative review of the available research evidence on the impact and factors contributing to impact of open access youth work upon young people (Hill, 2020) proved helpful in terms of selecting studies that were investigating the same topic.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Professional youth work in Western welfare states is known as a developmentally appropriate practice that aims to prevent individual and social problems by supporting the personal development and social participation of youngsters. Although professional youth work has often been claimed to have a positive impact on young people's development, research-based substantiation of the effects of the youth work process on specific outcomes and the positive development of youngsters is poorly developed in the literature (McGregor, 2015;Mundy-McPherson et al, 2012;Williamson & Coussée, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Of all of the articles in this special issue Mundy-McPherson et al (2012) provided the starkest depiction of what appears not only to be simply a gap but a chasm between one area of youth practice and intervention science. While such a chasm is evident in several fields, these authors focus was on interventions (including services and practices) referred to as youth work.…”
Section: Bridging the Gap Between Research And Practicementioning
confidence: 99%
“…The Mundy-McPherson et al (2012) article raises the need to develop research cycles that narrow the gap between laboratory settings and everyday service delivery contexts. An illustration of a framework that works in a different sequence than the widely used United States National Institutes of Health's intervention research cycle (see Mrazek and Haggerty 1994) is exemplified by designed based research (DBR), which is used in learning sciences (Design-Based Research Collective 2003).…”
Section: Bridging the Gap Between Research And Practicementioning
confidence: 99%
See 1 more Smart Citation